The common grammatical error in name among the Arab Twittered in Twitter - Al Anzi, Nujood Ismail Rafie; Abdul Jabbar, Mohammed Azidan (Journal of Humanities & Social Sciences, 2019)
Arabic is exposed to many negative linguistic manifestations, such as the phenomenon of widespread grammatical errorin social media, especially Twitter. The aim of the current study is to monitor grammatical errorin Twitter tweets and to identify factors affecting grammatical errorin Twitter tweets. The study also seeks to investigate the impact of grammatical variation on the understanding of tweets and to detect the effect of grammatical erroron Level level. In order to verify the validity of the hypotheses and to answer all the questions, the researcher will use the statistical analytical descriptive method in order to obtain the study data. The study will then devise a computer program designed by the researcher to correct common grammatical error among Twitter. The study sample will consist of only 200 informative tweets from 2016 to 2018, with many Arab political and social events occurring in this period, so Twitter has become an important and influential medium in the Arab world. The nature of the research requires that it be in four chapters, preceded by an introduction and followed by a conclusion.
Keywords: grammatical negligence; common; tweeters; twitter